Inflation, Liquidity and Innovation - Evers, Michael (World Bank, Washington, DC, 2018)
This paper presents a simple model with financial frictions where inflation increases the cost faced by firms holding liquid assets to hedge risky production against expenditure shocks. Inflation tilts firms' technology choice away from innovative activities and toward safer but return-dominated ones, and therefore reduces long-run growth. The theory makes specific predictions about how the severity of this adverse effect depends on industry characteristics. These predictions are tested with novel harmonized firm-level data from 139 developing countries, overcoming small sample problems constraining previous work. The analysis finds that inflation affects the composition but not the overall quantity of investment. A one percentage point increase in inflation reduces the establishment-level probability of innovation by 4.3 percent but does not affect total investment. Moreover, innovating firms display a stronger dependence on liquid assets, which, in turn, are negatively related to inflation. Generalized difference-in-differences estimations corroborate the sector-specific predictions of the theoretical model.